1986
DOI: 10.3109/01913128609014587
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter-Like Organisms and Surface Epithelium Abnormalities in Active, Chronic Gastritis in Humans: An Ultrastructural Study

Abstract: A prospective light and electron microscopic study of repeated endoscopic gastric biopsy specimens obtained from 10 patients presenting at the first examination for long-standing erosive gastritis was performed. In nearly all specimens from 7 patients, spiral bacteria were found in close contact to the surface epithelial cells and associated with active inflammatory changes. These organisms appeared similar to those recently described as gastric "campylobacter-Like organisms" (GCLO). It is possible that they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
2

Year Published

1991
1991
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(58 citation statements)
references
References 10 publications
5
50
2
Order By: Relevance
“…Thus, the presence of different cell adherence forms of H. pylori has been correlated with cytolysis and disintegration/destruction of the gastric epithelium (3,11,13). Another feasible indirect mechanism of action is the recruitment and activation of inflammatory cascade(s) with potent chemokines (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the presence of different cell adherence forms of H. pylori has been correlated with cytolysis and disintegration/destruction of the gastric epithelium (3,11,13). Another feasible indirect mechanism of action is the recruitment and activation of inflammatory cascade(s) with potent chemokines (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results have often been discordant and in part difficult to interpret: different study models were applied, involving animal cells (14), cultured human gastric cells (9), gastric cancer cell lines (17, 21, 31), as well as tumour cell lines of other origin (18,19,22). Some investigations used live cells from patients with dyspepsia (3, 10) or gastritis (5,7,8,11,13), and only a few have included test materials from patients with gastric or duodenal ulcers (6,20). Studying adherence of H. pylori using cell lines, especially of non-gastric origin, has obvious limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 The existence of H. pylori in the parietal cell canaliculi in humans has also been reported. 14,50,51 The results of an ultrastructural quantitative study reported by Taniguchi et al 52 indicated that there was nearly one H. pylori per 100 parietal cells, and all of the H. pylori in the canaliculi appeared intact. Using immunoelectron microscopy, we found H. pylori in the parietal cell canaliculi that were morphologically similar to those found deep in the glands or in the mucous layer.…”
Section: Intestinal Metaplasiamentioning
confidence: 99%
“…11 H. pylori is generally observed only in the gastric mucous layer or in the spaces between gastric mucus-secreting cells, and not in the gastric epithelial cells or the lamina propria. 12 Although in the 1980s investigators emphasized the absence of H. pylori within the lamina propria, [13][14][15] the presence of H. pylori within the lamina propria of the human gastric mucosa was described in the 1990s. Both whole H. pylori and H. pylori-immunopositive material are found in the lamina propria of biopsy specimens from H. pylori-positive patients.…”
mentioning
confidence: 99%